RTB EAGEL Documentary - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2024)
RTB-EAGEL aims to provide services such as pathogen diagnostics, virus-elimination, in vitro and germplasm exchange services as well as a platform for Roots, Tubers and Bananas (RTB) research and knowledge sharing, on a regional basis. By enabling the safe and efficient exchange of roots, tubers and bananas (sweet potato, potato, cassava, yams and bananas) between CGIAR breeding programs and regional National Agricultural Research & Extension System (NARES) partners for local field evaluations, it is anticipated that new varieties will be released, and get into the hands of farmers, more quickly than is currently happening. The exact timeframes for this varies according to crop, but will ultimately result in increased productivity. In addition, RTB-EAGEL will supply, on request, ‘nucleus’ high-quality disease-free plantlets of the best varieties, for further mass-propagation, in seed systems. This will accelerate the selection, delivery and widescale adoption of a steady stream of new RTB crop varieties. It will offer state-of-the-art technology for capacity development and research and knowledge-sharing regionally